Disponibilidad del recurso hídrico en la subcuenca del Río Corredores para establecer un mecanismo de control en el aprovechamiento del caudal disponible, mediante un balance hídrico superficial e integrado - Godinez-Benavides, Jordan (Instituto Tecnológico de Costa Rica, 2018)
The following study was carried out for the Corredores river sub-basin, belonging to the Corredor canton in the south of the country, developed with the purpose of contributing to the management of water resources in the area by the Water Directorate (DA), Ministry of Environment and Energy (MINAE). For this hydrological system, hydric availability is estimated through a water balance, the information registered in the database of the DA corresponding to concessions granted can be used, as well as inspections for the registration of illegal users in the area were planned, finding a total of 12 at the surface level, of which an annual volume of consumption was obtained at a surface level of 0,118 ℎ𝑚3/year. Starting from this moment and assuming that the scenario is close to the water balance with the people closest to reality, the volume of runoff from the waters below the sub-basin was obtained with a value of 368.79 ℎ𝑚3/año. He mentions that this scenario was used as the basis for the calculation, since at present in the subbasin their presence of illegal users, so it resembles the reality, however it must be said that the number of these users is estimated is much greater than 12 in the sub-basin. On the other hand, an integrated water balance was carried out, which works with surface and underground variables, obtaining a value without illegal users of 370.88 ℎ𝑚3/año at the exit of the sub-basin and 370, 428 ℎ𝑚3/year contemplating illegal users. There are channels belonging to the company Palma Tica S.A in the lower part of the sub-basin, which contribute to runoff. By dividing the subbasin into microbasins, it was possible to determine the contribution of these channels by means of a difference in volumes, between the total volume contributed and the volume generated by the sections, obtaining a value of 57.11 ℎ𝑚3/year, which corresponds to 15.48% of the volume downstream of the total sub-basin In reference to water availability, the Corredor River has a flow of 331,8810.52 ℎ𝑚3/year in its main channel and in the same way it was calculated for its tributaries, leaving 10% of the environmental flow. In the social field, there is a notorious problem in the lower part of the sub-basin in the rainy season due to flooding, in turn problems of lack of potability, as well as isolation of society due to flooding of the river At the sub-basin level, there was a problem of ignorance about the functions of the DA and the existence of the Water Law, where 92% of respondents do not know this entity. The DA is not receiving, for illegal use, an approximate amount of money of 680,456 colons belonging to the Canon for Harvesting, which means that if the available flow in the sub-basin were granted, there would be an annual amount of 366,540,344 colons
Proyecto de Graduación (Licenciatura en Ingeniería Agrícola) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Agrícola, 2018
Keywords: Gestión; Balance hídrico; Cuencas; Variables; Volumen